Wireless power transfer - Khandaker, Tahsin; Alam, MD. Mahmudul; Zaheen, M. Sajib; Chowdhury, Dipta (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.